Design, synthesis, and molecular docking of novel pyrimidine-hydrazone hybrids bearing sugar moieties as potential antioxidant agents - Haider M. Hassan; Mohammed Abbas Al-Silaykhee; Buraq Safaa Alasadi (CV. Literasi Indonesia, 2026)
A novel series of 5-bromo-2-(methylthio)pyrimidine-4-carboxylic acid derivatives conjugated with monosaccharides was synthesized and evaluated in vitro for their antimicrobial and antioxidant activities. Initially, the core scaffold, 4 5-bromo-2-(methylthio)pyrimidine-4-carboxylic acid, was prepared in a single step via the condensation of 5-bromo-2-(methylthio)pyrimidine-4-carboxylic acid with hydrazine hydrate. Subsequently, the resulting hydrazide derivative was successfully condensed with various monosaccharides under Schiff base reaction conditions. Biologically, the total antioxidant capacity of the synthesized compounds was evaluated using the phosphomolybdate assay. The obtained results revealed encouraging antioxidant profiles for several derivatives, demonstrating potent EC50 values comparable to the standard reference, ascorbic acid.